A Compact Quadruplexer-Integrated Filtering Power Divider - Chi-Feng Chen; Kai-Wei Zhou; Ruei-Yi Chen; Hsin-Ya Tseng; Yi-Hua He; Wen-Jie Li; Wei-Cheng Jiang (IEEE Journal of Microwaves, 2021)
A compact quadruplexer with the functions of frequency division, frequency selection, and power splitting/combining is presented in this article. Four tri-mode stub-loaded resonators were adopted to construct the compact multifunctional quadruplexer with a third-order filtering response. The four-channel passbands of the quadruplexer were controlled and realized independently by using the distribution coupling configuration. The output coupling structure was designed to be symmetrical with equal power division for each channel. To achieve a satisfactory isolation performance, a resistor was loaded between the open ends of the output coupled lines for each channel. A microstrip multifunctional quadruplexer operating at 1.1, 1.44, 1.73, and 2.06 GHz was fabricated. The prototype circuit size of the multifunctional quadruplexer was only approximately 0.4 λg × 0.59 λg. Moreover, the output isolations were >27 dB within the entire frequency bands.